Propagacion in vitro de Hippeastrum sp. - Vargas C, T.E.=700 1 Oropeza C, M.; De Garcia, E.
(En, Es)
ilus., 8 ref.
Keywords: MICROPROPAGACION; CULTIVO IN VITRO; AMARYLLIDACEAE; VENEZUELA; HIPPEASTRUM; AGRONOMIA TROPICAL